Améfrica in letters : literary interventions from Mexico to the Southern Cone - Gómez Menjívar, Jennifer Carolina; Badiane, Mamadou (Hispanic issues (Vanderbilt University), 2022)
"This book examines the work and influence of under-studied Black writers in Latin America"--